Clinicians’ attitudes and knowledge of medicinal cannabis in opioid dependence treatment clinics in New South Wales, Australia - Laila Parvaresh; Llewellyn Mills; Jaleh Gholami; Louisa Jansen; Nazila Jamshidi; Kate Baker; Christopher Tremonti; Marguerite Tracy; Adrian Dunlop; Nicholas Lintzeris (Journal of Cannabis Research)
Abstract Background There are no prior studies investigating the attitudes and knowledge of opioid treatment program (OTP) clinicians on prescribed medicinal cannabis in OTP clients. This study examined the OTP clinicians' medicinal cannabis experience, knowledge, concerns, and educational needs. Methods Staff from six public OTP services in New South Wales completed a medicinal cannabis survey. Staff included nurses, doctors, pharmacists, allied health, and consumer workers. Single-level regression models were used to estimate participants’ sex, role, and year of experience effect. Results 102 (63%) clinicians responded to the medicinal cannabis part of the survey, mostly female (n = 58, 56.9%), and more than half worked full-time (n = 54, 52.9%). Most of the participants (88.5%, 85/96) lacked experience providing medicinal cannabis, two in three (66.7%, 68/102) agreed to consider medicinal cannabis as a treatment for addressing cannabis use in OTP clients. Over 70% (71.5%, 73/102) expressed similar agreement to consider medicinal cannabis for other health conditions in OTP clients. More than half of the clinicians (54.2%, 52/96) expressed a lack of confidence in assisting clients with accessing medicinal cannabis, and were unfamiliar with current regulations (56.2%, 54/96). Clinicians expressed safety concerns regarding side effects such as driving-related problems (74%, 71/96), cognitive impairment (54.2%, 52/96), and cannabis dependence (54.2%, 52/96). The three conditions most endorsed as having sufficient evidence to support the use of tetrahydrocannabinol (THC)-based medicinal cannabis were palliative care symptom management (72.4%, 71/98), chronic pain (67.4%, 66/98), and multiple sclerosis (43.8%, 43/98). The three conditions most identified as having sufficient evidence to support the routine clinical use of cannabidiol (CBD)-based medicinal cannabis were chronic pain (64.9%, 63/97), palliative care (62.5%, 60/96), and sleep problems (44.8%, 43/96). The most common educational needs identified by participants were the evidence for the effectiveness of medicinal cannabis in cannabis dependence treatment (88.5%, 85/96), other health conditions (87.5%, 84/96), and indications and contraindications for using medicinal cannabis (87.5%, 84/96). Conclusion Despite the interest in using medicinal cannabis for treating cannabis dependence and /or other health conditions, clinicians identified several barriers including limited experience, lack of confidence, and poor understanding of the regulatory framework.